Core–shell colloidal particles with dynamically tunable scattering properties. Issue 37 (13th September 2017) - Meng, Guangnan; Manoharan, Vinothan N.; Perro, Adeline
Abstract : Polystyrene-hydrogel core–shell particles exhibiting a transition from Rayleigh to Mie scattering are created. Optical measurements show that the transition is controlled by varying temperature or ionic strength. Such core–shell particles may find use as optical switches or optical filters with tunable opacity. Abstract : We design polystyrene–poly( N ′-isopropylacrylamide- co -acrylic acid) core–shell particles that exhibit dynamically tunable scattering. We show that under normal solvent conditions the shell is nearly index-matched to pure water, and the particle scattering is dominated by Rayleigh scattering from the core. As the temperature or salt concentration increases, both the scattering cross-section and the forward scattering increase, characteristic of Mie scatterers. The magnitude of the change in the scattering cross-section and scattering anisotropy can be controlled through the solvent conditions and the size of the core. Such particles may find use as optical switches or optical filters with tunable opacity.